Damages associated to 1995-2006 floods and flash-floods in the east of the Apuseni Mountains - Arghiuş, Viorel; Ozunu, Alexandru; Ştefănescu, Lucrina; Costan, Camelia; Arghiuş, Corina (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2010)
During 1995–2006, the Eastern Apuseni Mountains was affected by floods which generate damages almost every year, observing an increase of their frequency towards the end of the mentioned period, when, in only two years (2004–2005), there were manifested nine episodes of such phenomena. The damages analysis was achieved by direct questioning, based on the observation data and reports of the County Inspectorates for Emergency Situations and other competent authorities during the period 1995–2006. Counting the direct damages generated by the floods in the region during the above mentioned period, the total summed 75.624 million US dollars. Among the main socio-economic objectives, traffic infrastructure proved to be by far the most susceptible to the unfavorable action of the floods (72.1% of the damages overall).
Keywords: floods; damages; the Apuseni Mountains